Cardiovascular disease risk and its determinants among hypertensive patients in Eastern Ethiopia: an institution-based cross-sectional study - Seid Yimam Ali; Seid Mohammed Abdu; Mekonin Meskelu Shegere; Abdifatah Abdulahi; Ahmed Abdikadir Hussein; Abdulahi Hussen Abdinur; Abdurahman Aden Muhumed; Zerihun Abera Ayele; Dawit Abebe; Workineh Diriba Gemechu (BMJ Open)
Objectives This study aims to assess the level of cardiovascular disease (CVD) risk and its associated determinants among hypertensive patients in Jigjiga, Somali Region, Ethiopia using the WHO 10-year CVD risk score.Design An institution-based cross-sectional study design was employed.Setting Hypertensive patients aged 40–74 years in two public hospitals in Jigjiga, Somali Region, Ethiopia, from 20 December 2023 to 20 February 2024.Participants Randomly selected 344 hypertensive patients aged 40–74 years with a duration of 1 year or more from the time of diagnosis and at least having 6-month follow-up.Primary outcome measures 10-year CVD risk level was assessed by using WHO 10-year CVD risk score. Risk levels were categorised as low (<10%) and high (≥10%).Secondary outcome measures Associated factors influencing CVD risk.Results The study included 341 hypertensive individuals, with a 99.1% response rate. Of the respondents, 58.9% were men. The overall prevalence of CVD risk within the coming 10 years was 134 (39.3%; 95% CI: 34.1% to 44.5%). Multivariable logistic regression analysis identified age, khat chewing, smoking and comorbid conditions as significant independent predictors of CVD risk. Specifically, individuals aged 60–69 years had an adjusted OR (AOR) of 3.97 (95% CI: 1.94 to 8.16) and those aged 70–74 years had an AOR of 2.99 (95% CI: 1.57 to 5.71). Khat chewers had an AOR of 2.58 (95% CI: 1.22 to 5.46), smokers an AOR of 3.44 (95% CI: 1.59 to 7.48) and individuals with comorbidities an AOR of 2.42 (95% CI: 1.47 to 3.99).Conclusion There is a significant increase in 10-year CVD risk among hypertensive patients in the study area. Age, khat chewing, smoking and comorbidities were independent predictors. Regular CVD risk screening for older patients, focused health education to reduce khat and tobacco use and integrated management of comorbidities are essential to lower future cardiovascular risk.